Evolution of small reservoirs in Burkina Faso - Forkuor, Gerald; Cofie, Olufunke O.; Barron, Jennie (CGIAR Research Program on Water, Land and Ecosystems, 2019)
Small reservoirs (SRs) are important infrastructures for providing water for a wide range of activities in Burkina Faso and other semiarid environments. In recent years, SRs have become even more important, considering the effects of climate change and variability such as erratic rainfall patterns, recurrent droughts and floods, delays in the onset of the rains (Laux et al. 2008), increased incidence of in-season dry spells (Lacombe et al. 2012), and high evapotranspiration rates. SRs provide vulnerable rural communities with water for multiple purposes, including domestic and agricultural uses (McCartney et al. 2012; Venot et al. 2012). However, a number of external factors are negatively influencing the sustainable uses of SRs. Rapid population growth (Zuberi and Thomas 2012) and its attendant human-induced activities are a threat to the quality of water in SRs, as are agricultural extensification and intensification around SRs, including the increased use of inorganic fertilizers.